A Cross-Cultural Analysis of Humanistic Education: Exploring Restorative Practices in Australian Education and The Parenting System of Islamic Education (Pesantren) in Indonesia - Fitriatin, Nur (Proceedings of Annual Islamic Conference for Learning and Management, 2025)
: This research intends to conduct a cross-cultural analysis of humanistic education, by exploring fundamental concepts of Restorative Practices in the Australian education system and the parenting system within Islamic education (pesantren) in Indonesia, addressing three primary research questions: (1) What are the core concepts of restorative justice within the Australian education system and the parenting system in Islamic education in Indonesia? (2) How do restorative practices within these systems align with the principles of humanistic education? (3) What are the similarities and differences in restorative practices between the Australian education system and the parenting system in Islamic education in Indonesia? The research will be conducted using qualitative methods and descriptive analysis to get the data from various sources, including interviews with education practitioners, observations, and in-depth literature studies. The finding will provide an in-depth insight into the practices of humanistic education, with a particular emphasis on efforts to restore relationships in the formal education contexts in Australia and the nurturing environment within Islamic education (pesantren) in Indonesia. The outcomes of this research are expected to make a significant contribution to the understanding of restorative practices in education and after valuable insight into how culture influences humanistic education. It can be used to enhance educational practices in both countries and identify potential cultural collaborative opportunities in educational contexts.